2013
DOI: 10.1016/j.ypmed.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Is wearing a pedometer associated with higher physical activity among adolescents?

Abstract: ObjectiveTo examine whether wearing a pedometer was associated with higher objectively-measured physical activity (PA) among adolescents independent of other behavior change strategies, and whether this association differed by sex or day of wear.MethodIn a parallel-group population-based cohort study, 892 adolescents (43.4% male, mean ± SD age, 14.5 ± 0.5 years) from Eastern England were recruited. PA was measured (in 2005–2006) by accelerometry over four days; a sub-group (n = 345) wore a pedometer coterminou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
30
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 30 publications
(27 reference statements)
6
30
0
2
Order By: Relevance
“…This may be due to the novelty of the new technology piquing the students' interest followed by the eventual, yet relatively quick, return to normal levels. Prior research examines the motivational effect of activity monitors showed a significant decline in PA from the beginning to the end of data collection (Ho et al, 2013), mirroring data in this research. Ho et al (2013) showed that girls who wore an activity monitor had more steps than those who did not.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…This may be due to the novelty of the new technology piquing the students' interest followed by the eventual, yet relatively quick, return to normal levels. Prior research examines the motivational effect of activity monitors showed a significant decline in PA from the beginning to the end of data collection (Ho et al, 2013), mirroring data in this research. Ho et al (2013) showed that girls who wore an activity monitor had more steps than those who did not.…”
Section: Discussionsupporting
confidence: 65%
“…Prior research examines the motivational effect of activity monitors showed a significant decline in PA from the beginning to the end of data collection (Ho et al, 2013), mirroring data in this research. Ho et al (2013) showed that girls who wore an activity monitor had more steps than those who did not. It is difficult to generalize findings from the current study as it spanned a considerably longer period of data monitoring than past studies using accelerometers.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, the estimates of physical activity across the week might be alarmingly lower than what was observed in this study as the pedometer for adolescents and adults often report increased step count per day just by wearing it. This behaviour is called reactivity and is commonly reported especially among female pedometer users [27]- [29]. In other words, it was very likely that Malaysian student nurses did even less walking than was recorded by the pedometer.…”
Section: Discussionmentioning
confidence: 99%